POSSIBILITIES OF USING INNOVATIVE TECHNOLOGIES IN MOTHER TONGUE CLASSES IN GENERAL SECONDARY EDUCATION - Maxkamova Guluzroxon Abdumutalibovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article provides methodological recommendations about effective methods of teaching using innovative educational technologies in general secondary education mother tongue classes, and from this, the topics given in the new generation textbooks based on the National Curriculum are taught to the students. useful recommendations are given in teaching